منظاور الفقه اإلسالمي ;وضمان صالحية املبيع ;اجلاواز الرتوجيية - Zawawi Abdul Wahid (Jurnal Hukum Islam, 2012)
In Islamic contract law, the third pillar is the existence of the object of the contract (mahal al-aqdi). The object of the contract becomes the target will be achieved by the parties through the stipulation of the contract. The object of the contract consisting of several components can be formed from two elements, namely elements which is the main target & objective of the contract and the elements of tabai' serves as a complement & complement to the main elements. Each Each of these two elements has a different legal impact, among them are things that are conditions for the validity of the contract fulfilled by the main elements, is not a requirement for the tabai' element, that is also indicators that cause a contract to be invalid such as usury, gharar, qimar if it is located in the main element causes the contract to become fasid, but has no effect if it is in the tabai' element. Naturally all of this with certain conditions (dhawabith) so as not to cross the line maqashid sharia. This article attempts to explain the extent of the impact the law of the tabai' principle in the product sales system that is equipped with guarantees and promotional gifts of various types and The form aims to increase sales results.